Hubungan Kualitas Pelayanan Terhadap Kepuasaan Ibu dalam Menggunakan Alat Kontrasepsi di Klinik Siloam Kecamatan Siantar Barat Kotapematangsiantar Tahun 2023 - Epi Ida Lestari Samosir; Asnita Sinaga; Isyos Sari Sembiring; Indra Agussamad (Asosiasi Riset Ilmu Kesehatan Indonesia, 2023)
Satisfaction is a person who has compared in terms of performance and also the expected results through the level of a person's feelings. In another theory written by Wilton, it is stated that satisfaction or dissatisfaction is the result of the final evaluation of the customer's response, namely the suitability that has been felt by the customer with the expected performance of the product that can be felt after the customer uses it. (Abarca 2021) Family planning is an effort by husband and wife to measure the desired number and distance. The effort in question includes contraception or pregnancy prevention and family planning. The basic principle of contraceptive methods is to prevent male sperm from reaching and fertilizing a woman's egg (fertilization) or preventing a fertilized egg from implanting (attaching) and developing in the uterus (Th. Endang Purwoastuti, 2016).From a preliminary survey in January 2023 at the Siloam Clinic, West Siantar District, Pematangsiantar City, 20 women of childbearing age were found, of whom 7 people expressed dissatisfaction with contraceptive services. Based on the background description, researchers are interested in taking the title The Relationship between Service Quality and Mother's Satisfaction in Using IUD Contraception at the Siloam Clinic, West Siantar District, Pematangsiantar City in 2023